Analysis of the ulun tagom concept (putra regional) in lumbis pasiangan office performance management, Nunukan district, North Kalimantan - Lumbis Lumbis; Zainur Hidayat; Nurul Hidayat (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The purpose of this research is to examine and find out the principles of the concept of